The assessment of the impact of anorexia nervosa on the vocal apparatus in adolescent girls – A preliminary report. (June 2016) - Maciejewska, Barbara; Rajewska-Rager, Aleksandra; Maciejewska-Szaniec, Zofia; Michalak, Michał; Rajewski, Andrzej; Wiskirska-Woźnica, Bożena
Abstract: Background: Chronic undernourishment in the course of anorexia nervosa leads to various metabolic and hormonal changes, which translates to the impaired functioning of the majority of systems and internal organs. The impact of eating disorders on the condition of the vocal apparatus has been described in the literature; nevertheless, it concerns mainly bulimia nervosa. Objectives: assessment of the vocal apparatus in adolescent girls diagnosed with anorexia nervosa from the point of view of possible influence on the function and structure of the larynx, low body mass accompanying anorexia, as well as energy deficiency, hormonal and emotional disturbances. Materials and methods: The research included 41 girls aged 12–19 years, diagnosed with anorexia, who were assessed for the condition of the vocal apparatus, using the perceptual assessment of voice according to GRBAS scale, videolarynostroboscopy, acoustic assessment, and voice self-assessment in Jacobson's VHI scale (voice handicap index). Results: The perceptual assessment of voice using the GRBAS scale revealed that changes in voice were mainly weak, asthenic in nature (70.73%) and there was also the feature of puffing perceived in voice (41.46%). In voice self-assessment with the use of VHI, most subjects seemed to point to changes of voice self-perception in emotional subscale (68%). Videolaryngostroboscopy revealed some features of functional disturbances of voice in more than half of subjects, mainly in the form of hyperfunctional dysphonia (31.78%). The maximal phonation time was significantly shorter, in proportion to duration of the primary disease. In the acoustic analysis, the decrease in the basic frequency F0 and narrowing of the voice scale were observed. 55% of older, post-adolescent patients presented with the structure of the larynx that was inappropriate for their age. Conclusions: These results might indicate that anorexia nervosa could have led to the structural and functional changes in the vocal apparatus. Such disturbances may be explained by the hormonal dysfunctions as well as starvation. Hormonal substitution at the appropriate time might be beneficial for the structure and phonation function of the larynx in girls with AN.